PARENT CONTROL RELATIONSHIP IN USE GADGETS WITH THE RESPONSIBILITY OF LEARNING CHILDREN AT RA MIFTAHUL ANWAR PADEMANGAN NORTH JAKARTA - Nurmaliyah, Yayah; Putri, Syifa Fauziyah (Journal of Early Childhood Education (JECE), 2023)
The aim of this study was to examine the relationship between parental supervision of gadget usage and children's learning responsibility. The research was conducted at RA Miftahul Anwar in Pademangan, North Jakarta. The research method used was quantitative, and the study design was correlational. The participants of the study were all the parents of students at RA Miftahul Anwar, totaling 23 individuals, and the sampling technique used was total sampling or saturated sampling. The data collection technique employed was a questionnaire consisting of items related to parental supervision of gadget usage and children's learning responsibility. The data were analyzed using the Pearson product-moment correlation with SPSS 22.The results of the study showed a correlation coefficient of 0.662 and a significance value of 0.001 < 0.05. Additionally, the calculated t-value (4.045) was greater than the tabulated t-value (2.080). Therefore, it can be concluded that there is a significant relationship between parental supervision of gadget usage and children's learning responsibility.